The htrM gene, whose product is essential for Escherichia coli viability only at elevated temperatures, is identical to the rfaD gene. - Raina, S (1991)
We have identified a new E. coli gene, htrM. The htrM gene was identified because its insertional inactivation by the Tn5 transposon results in E. coli's inability to form colonies at temperatures above 43 degrees C. The corresponding htrM+ gene was cloned on the basis of its ability to correct the temperature-sensitive phenotype of the htrM::Tn5 insertion mutations. The htrM gene has been mapped to 81.2 min on the conventional E. coli genetic map. It was sequenced and shown to code for an acidic, 34,893-Da polypeptide. Three transcriptional starts were located 48, 90 and 123 nucleotides upstream of the ATG, initiation codon referred to as the P1, P2 and P3(hs) promoters, respectively. The -10 and -35 regions of the P1 promoter bear a close similarity to the E sigma 70-recognized consensus sequences, while the -12 region of the P2 promoter resembles the consensus promoter sequence transcribed by the rpoN gene product. Transcripts of the htrM gene accumulate with increasing temperature. The -10 and -35 regions of the P3(hs) promoter, represented by nucleotides 160 to 130 upstream of the ATG initation codon, are similar to the E sigma 32-recognized consensus sequences. The sigma 32 transcription factor is essential for maximal htrM gene transcription, since htrM RNA transcripts are made at reduced rates in a rpoH null mutant background. Surprisingly, the htrM gene turns out to be identical to rfaD, whose product is required for the biosynthesis of the ADP-L-glycero-D manoheptose lipopolyaccharide precursor [Pegues et al. (1990) J. Bacteriol. 172, 4652-4660].